A cross-sectional study on impact of online classes among undergraduate students of Shimoga institute of medical science, Shivamogga due to COVID-19 - B. P., Anitha; Kumar N., Praveen; R., Darshitha; Kiran G. M., Shashi (International Journal Of Community Medicine And Public Health, 2022)
Background: The COVID-19 has resulted in shutdown of all the schools all over the world. This has led globally, over 1.2 billion children to remain out of classroom. As a result, education has changed from classroom teaching to e-learning, whereby teaching is on digital platforms. Although online classes have several advantages but there are disadvantages also. In this regard the study aims to explore whether the online classes effect on both physical and mental health of students along with the effect on education. Methods: A cross-sectional study was done from October-November 2020 (2 months). A pre-designed questionnaire was given to phase-III, part-I and part-II students (253) in Google forms. The database was created in MS-excel sheet and results were expressed in percentages. Results: Out of 253 students 166 students responded, which was 65.6% out of whom physical health impact like eye problems due to online-classes was most for dry eyes (54.8%) and least for double vision (13.9%). Impact on mental health was most for headache (54.8%) and least for depression (36.7%). Impact on education was most for lack of practical based learning (97.6%) and was less for difficulty in understanding subject (63.9%). Conclusions: Students had more negative impact on education with online-classes. So, except during crisis period offline classes are preferred.